Perbandingan Metode SDI dan RCI Pada Survey Data Kondisi Jalan Kabupaten Di Kabupaten Subang - Hasanudin; Adi Subandi; Nandang Muhyidin (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2023)
The technical data used is road condition data for 2022 by taking samples on several road sections to compare the survey process, analysis and results of road condition data between the International Rougnees Index (IRI) and Surface Distress Index (SDI) approach methods in accordance with the objectives of the implementation. this final assignment. The comparison was carried out to determine the best method approach applied to district roads in Subang Regency. In surveying road condition data, using the Surface Distress Index (SDI) method and the International Roughness Index (IRI) method obtained from the results of the Road Condition Index (RCI) survey. Judging from the implementation of the survey, the two methods have significant differences according to field data collection and Judging from the results of calculating road condition data based on both methods on the sample road sections, the Subang - Bantarsari Road section has similar road damage conditions.